2018
DOI: 10.1016/j.bbmt.2018.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prophylactic Foscarnet on Human Herpesvirus-6 Reactivation and Encephalitis in Cord Blood Transplant Recipients: A Prospective Multicenter Trial with an Historical Control Group

Abstract: Cord blood transplantation (CBT) is a distinct risk factor for human herpesvirus-6 (HHV-6) reactivation and HHV-6 encephalitis. In a prospective multicenter trial we investigated the effects of prophylactic foscarnet (90 mg/kg i.v. infusion from days 7 to 27 after CBT) on the occurrence of HHV-6 reactivation, HHV-6 encephalitis, and acute graft-versus-host disease (aGVHD) in CBT recipients. Between 2014 and 2016, 57 patients were included in a foscarnet-prophylaxis group. Outcomes were compared with an histori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…It is well known that CBT is a risk factor for post-transplant HHV-6B encephalitis, 44 but none of the 61 CBT patients without prophylactic or preemptive antiviral treatments for HHV-6 infection developed encephalitis in this study. Although prophylactic or preemptive antiviral treatments have previously been administered to reduce the risk of post-transplant HHV-6B encephalitis in adult CBT patients, 26,45 the present data raise doubts about similar interventions for all pediatric CBT patients. One study showed that the incidence of HHV-6B encephalitis declined after the introduction of prophylactic ganciclovir treatment in pediatric CBT patients;…”
Section: Ta B L E 3 Encephalitis/encephalopathy Cases With Hhv-6b Infmentioning
confidence: 66%
“…It is well known that CBT is a risk factor for post-transplant HHV-6B encephalitis, 44 but none of the 61 CBT patients without prophylactic or preemptive antiviral treatments for HHV-6 infection developed encephalitis in this study. Although prophylactic or preemptive antiviral treatments have previously been administered to reduce the risk of post-transplant HHV-6B encephalitis in adult CBT patients, 26,45 the present data raise doubts about similar interventions for all pediatric CBT patients. One study showed that the incidence of HHV-6B encephalitis declined after the introduction of prophylactic ganciclovir treatment in pediatric CBT patients;…”
Section: Ta B L E 3 Encephalitis/encephalopathy Cases With Hhv-6b Infmentioning
confidence: 66%
“…Although herpesvirus reactivation has been associated with mortality in various patient groups, clinical trials involving liver transplant and HCT patients that have studied HHV-6 antiviral prophylaxis or a preemptive strategy (using antivirals or immunosuppression reduction) have not demonstrated clinical effectiveness (even when HHV-6 reactivation is reduced). 2,5,6 Moreover, no high-quality data support the use of antiviral treatment for HHV-6-associated syndromes. New approaches, including characterizing host responses to viral infections in immunocompromised hosts, are needed to help us better determine causality.…”
Section: Hhv-6 and Septic Shock: Tenuous Proof Of Causationmentioning
confidence: 99%
“…There was no difference in the virological response to antiviral treatment between the CBT and non‐CBT cases. Moreover, efficacious strategies for prevention of HHV‐6 encephalitis have not yet been established …”
Section: Discussionmentioning
confidence: 99%